PENERAPAN SOMATIC AUDITORY VISUALIZATION INTELLECTUALLY (SAVI) MENGGUNAKAN CD INTEAKTIF TERHADAP HASIL BELAJAR - Vivi Putri Utami; Miterianifa Miterianifa (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
Abstract This research was instigated by the low achievement on Atomic Structure material of X grade students at State Agricultural Integrated Vocational High School in the Academic Year of 2015/2016. This research was an experiment. This research aimed at knowing how the effect of using Somatic Auditory Visualization Intellectually (SAVI) learning model with Interactive CD about Atomic Structure toward  students’ Achievements was. The research design was using pretest and posttest. The sample technique of this research was Simple Random Sampling. X ATPH 1 was the experimental group and X ATPH 2 was the control group. The techniques of collecting data were by measuring the homogeneity test as the preliminary data in the previous material (introduction to chemistry), Interview, documentation, observation, pretest and posttest as the final data. The data were analyzed by using T-test formula. The final calculation state that tobserved  2,401 was higher than ttable 2,00 at 5% significant level. It revealed that H0 was rejected and Ha was accepted. The research findings showed that (1) Somatic Auditory Visualization Intellectually (SAVI) Learning Model with Interactive CD about Atomic Structure  Influenced Students’ Achievement, (2) the influence of using Somatic Auditory Visualization Intellectually (SAVI) Learning Model with Interactive CD about Atomic Structure  Influenced Students’ Achievement was 7,7%. Keywords: Cooperative Learning Model, Achievements, Somatic Auditory Visualization Intellectually (SAVI), Interactive CD, Atomic Structure.